36‐2: Invited Paper: Self‐Alignment of Liquid Crystal for Multi‐Domain Liquid‐Crystal Display. Issue 1 (30th May 2018) - Lan, Song; Chen, Xingwu; Wei, Hongquan; Wu, Ling; Tseng, Te-Jen; Hsieh, Chung-Ching; Chen, Hsiao-Hsien; Lin, His-chien; Lee, Yung-Hui
Abstract : By introducing photopolymerizable amphiphile organic monomers(PAOM) into nematic liquid crystals (NLC) with controlled amount of UV‐curable reactive mesogen (RM), a amulti‐domain vertical‐alignment LC device was successfully demonstrated. The device, possessing a vertically aligned LC director in four different azimuthal directions, exhibited a fast response time, wide‐viewing‐angle characteristics and high voltage holding ratio(VHR), in the absence of conventional polyimides vertical‐alignment layers. The formation of automatic and robust vertical alignment layer was anlayzed by using scanning electron microscopy(SEM).